Perbedaan Hasil Belajar Siswa Yang Diajar Dengan Menggunakan Metode Ceramah Dan Team Quiz Mata Pelajaran Fikih - Ahmad Shofiyuddin (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
The purpose of this study is 1) to find out the learning outcomes of students taught using the lecture method on the subject of Jurisprudence on the subject of Hajj and Umrah in MTs Sunan drajat Banjarwati Paciran Lamongan 2) to find out the learning outcomes of students who were taught using the team quiz method for the subject of Jurisprudence on the subject of Hajj and Umrah MTs Sunan Drajat Banjarwati Paciran Lamongan 3) to find out the differences in the learning outcomes of students taught using the lecture method and the team quiz for Jurisprudence subjects on Hajj and Umrah Sunan Drajat Banjarwati Paciran Lamongan The research method used in this research is quantitative descriptive research location is MTs Sunan Drajat Banjarwati Paciran Lamongan. The population of this study is all students of class MTs Sunan Drajat in the academic year 2013-2014, amounting to 81 students. Data collection techniques using test methods (pretest and posttest) and documentation. Based on the results of tests that have been done, namely 1) learning outcomes using the lecture method with Hajj and Umrah material with an average value of 90.95 and a median value of 90 in other words students experience individual completeness by referring to KKM fiqh 75 or classical completeness with a percentage 100% completeness. 2) the average grade of students of MTs Sunan Drajat Banjarwati Paciran Lamongan an average of 89.23 and a median value of 90 in other words students experience individual completeness with reference to KKM fiqh 75. And students experience completeness with a percentage of completeness 100 %.